Introduction to ecology - Botkin, Daniel B. (Henry Stewart Talks, 2019)
The science of ecology, Saving Mono Lake: an example of ecology to solve an environmental problem, The basic concepts of ecology, Predators and prey: saving the wolves and moose of Isle Royale National Parks, Biodiversity and its advantages: examples from the African Serengeti